PARADIGMA SOSIALISASI DAN KONTRIBUSINYA TERHADAP PENGEMBANGAN JIWA BERAGAMA ANAK - Anwar, Anwar (AL-MAIYYAH, 2018)
This article examines the social capacities that become the potential of every human being in relation to the development of his religious soul. Humans are known as religious beings, meaning that in a human way humans make statements, agreements to believe in God, and this is a religious potential that needs to be maintained by a healthy and religious environment. When socializing, every human being is in an environment whose behavior patterns have been formed, and face a norm system that is used as a basis for interaction. Therefore, religious souls need an environment that can direct it to the right direction for growth, that is, the awareness of religion according to what has been pledged while still in the mothers womb.